العلاقات العسكرية المصرية – الروسية في عهد الرئيس عبد الفتاح السيسي (Al-Mostansiriyah journal for Arab and international studies, 2026)
Egypt maintained strong military relations with the Soviet Union, which clearly contributed to the advancement of its various armed forces and their effective and influential contribution to the Arab-Israeli wars of 1956, 1967, and 1973. Military relations between Egypt and Russia resumed during the era of President Mohamed Hosni Mubarak (1981–2011), who adopted a foreign policy different from that of his predecessor. However, they remained captive to the American determinant.Egyptian-Russian military relations witnessed a remarkable development after the revolution against the Muslim Brotherhood's rule on June 30, 2013, and the military coup against them. However, they did not escape the sphere of American influence, and Egypt sought to use Russia as a leverage to obtain various types of American weapons, a fact proven by evidence. Egyptian-Russian military cooperation encompasses multiple and diverse areas that benefit both parties. Joint cooperation agreements include arms deals of various types and purposes: army, navy, air force, and air defense; joint military exercises: Bridge of Friendship, Protectors of Friendship, and Arrow of Friendship; and unified efforts and positions to combat terrorism and extremism in all its forms and manifestations.